(untitled) (The Pakistan Development Review, 1989)
Providing employment opportunities in rural Pakistan has been on the policy agenda since the early 1970s when it was realized that the country’s reasonably good economic performance had virtually bypassed a significant proportion of people in the rural areas. The magnitude of the expanding labour force in view of the failure in the past to create adequate job opportunities poses a great challenge to the policy·makers to ensure job openings for the new entrants as well as for those who are presently unemployed and/or underemployed. This paper reviews some of the most important factors that have influenced employment creation in rural areas. Sections II, III, and N deal with the sectoral performance with respect to employ· ment in the agricultural sector, industrial sector and rural development respectively. The summary and conclusions are presented in the final section.